Consumer Preference for Mid-Cost Housing Based on Their Social Stratification in Special Region of Yogyakarta - Hidayati, Wahyu; Bagas, Bagaskara (EKO-REGIONAL, 2024)
Owning residential property with ideal location, physical characteristics, neighborhood, legal documents, amenities, proximity to public services, etc., on a housing development requires consumers to have the ability and willingness to pay for such attributes. However, the cost is relatively high while the budget is often restricted. In Special Region of Yogyakarta, housing backlog is caused by supply and demand gap for mid-cost housing, limited capacity of developers, and low housing affordability for low-income people. This research aims to analyze the influence of social stratification on consumer preference for mid-cost housing on housing developments and on non-clustered housing areas (on which the houses are not constructed by a single developer) as well as the desired attributes of mid-cost housing. This research employed descriptive and inductive statistics with chi-square test. Test of independence was used to analyze the variables to determine whether social stratification influences consumer preference for mid-cost housing on both areas. Purposive sampling was employed with a sample size of 220 respondents. The result showed H0 was rejected as χ² = 12.35 > χ² α; (r-1)(c-1) = 5.991, meaning social stratification influences consumer preference for mid-cost housing on both areas. The desired attributes included location, physical characteristics, legal documents, neighborhood, and amenities. In order that residential areas may contribute to regional development, it is important for the local government to implement relevant policies and mortgage financing policies as well as provide supporting infrastructure and facilities for its development.